Comparison phenotypic and genotypic identification of Staphylococcus species isolated from bovine mastitis - Felipe Freitas Guimarães; Samea Fernandes Joaquim; Marcela Pinho Manzi; Rodrigo Costa da Silva; Ariane Cristina Mendes de Oliveira Bruder-Nascimento; Elizabeth Oliveira Costa; Hélio Langoni (Pesquisa Veterinária Brasileira)
ABSTRACT: In addition to Staphylococcus aureus nowadays other coagulase-positive staphylococci (CoPS) and coagulase-negative staphylococci (CoNS), earlier considered of minor importance, are now accepted as relevant pathogens for humans and animals. The involvement of these microorganisms in bovine mastitis etiology and the possibility their transmission through milk to humans justify the requirement of developing reliable methods for identification of the most frequent species among them. The purpose of this study was to compare the phenotypic techniques with the genotypic method carried out by sequencing of the rpoB gene in identification of several species of the genus Staphylococcus isolated from bovine mastitis. A total of 300 staphylococci isolates of bovine mastitis cases from several Brazilian dairy herds were studied by phenotypic and genotypic techniques, respectively: 150 CoPS and 150 CoNS strains. A total of 18 CoNS different species and 4 CoPS species were identified. Among the CoNS the following species were recognized: 48 (32%) Staphylococcus warneri, 22(15%) S. epidermidis, 20(13%) S. hyicus, 10(7%) S. xylosus, 7(5%) S. haemolyticus, 6(4%) S. simulans, 6(4%) S. schleiferi subsp schleiferi, 6(4%) S. hominis, 5(3%) S. pasteuri, 4(2.7%) S. cohnii, 3(2%) S. saprophyticus subsp. saprophyticus 3(2%) S. chromogenes 3(2%) S. sciuri, 2(1%) S. saccharolyticus, 2(1%) S. lugdunensi, 1(0,7%) S. auricularis, 1(70%) S. saprophyticus subsp. bovis, 1(0.7%) S. capitis. And among the 150 CoPS were identified respectively: 105 (70%) S. aureus, 21(14%), S. hyicus, 19(13%) S. intermedius e 5(3%) S. schleiferi subsp coagulans. Considering the 150 CoNS isolates, the identifications performed by phenotypic and genotypic tests presented 96.7% of concordance, kappa coefficient of agreement = 0.933, SE (standard error) of kappa=0.021 (95% confidence interval: 0.893 to 0.974), Pearson’s correlation coefficient (r) = 0.9977, (confidence interval 95%: 0.9938 a 0.9992) and in relation to 150 CPS isolates it was detected an agreement of 98.7%, kappa = 0.960, SE of kappa = 0.016, (95% confidence interval: 0.929 to 0.992) Pearson’s correlation coefficient (r) = 0.9994 (95% confidence interval: 0.9681 to 1.0000). The verified agreement strength between the identification methods can be considered as excellent. These results assure that according to laboratory resources any of them will be suitable to perform the staphylococci identification.